Effect of Naringenin, Quercetin, and Sesamin on Xenobiotica-Metabolizing CYP1A and CYP3A in Mice Offspring after Maternal Exposure to Persistent Organic Pollutants. (8th May 2017) - Pilipenko, Nadezhda; Ropstad, Erik; Halsne, Ruth; Zamaratskaia, Galia
Abstract : The aim of the present study was to evaluate in vitro effects of dietary phytochemicals naringenin, quercetin, and sesamin on the activities of ethoxy- (EROD; CYP1A) and benzyloxy- (BROD; CYP3A) resorufin O-dealkylases after the exposure to the cocktail of persistent organic pollutants (POPs). CD-1 mice were exposed from weaning, through gestation and lactation to a defined mixture of POPs. Hepatic microsomes were prepared from their female offspring at postnatal day 42. Hepatic EROD and BROD activity were evaluated in the presence of quercetin, naringenin, and sesamin at nine concentrations from 5 to 100000 nM. EROD activity was strongly inhibited by quercetin with K i values from 1.7 to 2.6  μ M. BROD activity was inhibited by quercetin with K i values from 64.9 to 75.3  μ M and naringenin with K i values from 39.3 to 45.8  μ M. The IC50 and K i values did not differ between the groups of mice with different levels of POPs exposure in any of the experimental sets. Sesamin did not inhibit either EROD or BROD. We concluded that the interactions of quercetin and naringenin with CYP1A and CYP3A in mice liver were not affected by the levels of POPs exposure.